Analyzing The Characterization of Municipal Solid Waste in Da Nang City, Vietnam - Giang Minh Hoang; Cuong Dinh Le; Takeshi Fujiwara; Song Toan Pham Phu; Naoya Akasaki; Dinh Van Pham (Chemical Engineering Transactions, 2021)
Recently, most cities in Vietnam are facing waste problems that are mainly caused by the rapid increase of municipal solid waste (MSW) amount and the limitations of the MSW management system. This study aims to characterise the waste generation, composition and characteristics of MSW in Da Nang city, which is one of the five biggest cities in Vietnam. The current problems and challenges of MSW system are also analysed. The sampling survey was conducted in the dry and wet seasons in August and November 2018. The MSW was taken directly from trucks at the landfill site with the sample size by 500 kg/waste sources. This study shows that the simultaneous development of production, trade and service activities in the last decade has led to the speedy growth of waste by 9 %/y, and reached 1,073 t/d in 2018. In which, waste generated from industry and the hospitals account inconsiderable proportions by 3.9 % and 1.4 %. This study also indicated that the MSW generation rate from the urban areas is more than that of the coastal and industrial areas. For the composition of MSW, biodegradable waste and recyclables are the main components with the proportion of 54 % and 27 % of the total waste. While the waste composition almost do not differ considerably by seasons, the difference in the characteristics of waste is a consideration for the processing. The current problems and solutions to improve the MSW system toward sustainability are also discussed and suggested.